Investigation of TEC Changes on Magnetic Conjugate Pairs over the Africa Region during the Geomagnetic Storm of August 25-26, 2018 - Korlaelçi, Serhat (My University, 2023)
In this study, the electron transport process resulting from electromagnetic drift between two magnetic conjugate pairs over the African region during the August 25-26 2018 geomagnetic storm was investigated. The effects of geomagnetic conditions presented with Dst index and IMF Bz values on Total Electron Content (TEC) values at conjugate stations were compared separately for stormy and quiet periods. During the storm period, the effect of TEC values at stations in the northern hemisphere (Haifa and Djibouti) on the TEC values at stations in the southern hemisphere (Ambalavao and Malindi) is greater than the effect of TEC values in the southern hemisphere on TEC values in the northern hemisphere. According to this result, it can be said that the south-directed electromagnetic convection was more than the north-directed convection in the examined dates. When the coefficients are examined, it can be said that the interaction is more in the magnetic conjugate pair that is closer to the equator during the storm period, and the interaction is more in the magnetic conjugate pair that is far from the equator during the silent period. Considering the coefficients calculated for Dst and IMF Bz, it is seen that the TEC values are very small compared to their coefficients. From this it can be concluded that the effect of Dst and IMF Bz is much smaller than the effect of TEC values at a station on TEC values at its magnetic conjugates.
Keywords: Ionosphere; Autoregressive Distributed Lag; magnetic conjugate pairs; Total Electron Content; geomagnetic storm.